The impact of opiate cut-off values in urine samples: Evaluation of 8 years of data - OVAT, Duygu Yeşim; ASLAN, Rukiye; RESTOLHO, Jose; AKGÜR, Serap Annette (The Bulletin of Legal Medicine, 2025)
Objective: Opiates are one of the most abused drugs with growing concern.In recent years, it is seen that changes have been made to the cut-off values for opiates.The cut-offs for opiates in screening tests increased from 300 to 2000ng/mL.The aim of this study was to present the opiate results of 8-year study and to evaluate the data according to cut-off values increased from 300 to 2000 ng/mL.Methods: A total of 11,348 urine samples were analyzed between 2014–2021.Preliminary diagnoses, outpatient admissions, and toxicological test results were compared under two cut-offs. Screening tests were performed using immunoassay method (Randox Evidence and CEDIA), and confirmation analysis was conducted by Gas Chromatography-Mass Spectrometry (GC-MS). Results: At the 300 ng/mL cut-off value, 3.45% of the cases were opiate-positive. 69.1% of the cases were from addiction clinics, demonstrating the clinical importance of sensitive cut-offs in detecting substance use among patients requiring treatment. In this study, it is shown that 39.8% of cases requiring judicial action were missed when the cut-off value was raised to 2000 ng/mL, highlighting the risk of false negatives in forensic settings.Conclusion: The findings highlight that opiate cut-off values and analytical sensitivity may influence both medical evaluations and legal interpretations.
Keywords: Forensic toxicology; Cut-off values; GC-MS; Judicial implications; Urine drug testing; Opiates; Immunoassay